Analysis of thermal models to determine the loss of life of mineral oil immersed transformers - Mohammad Tolou Askari; Mohammad Javad Mohammadi; Jagadeesh Pasupuleti; Mehrdad Tahmasebi; Shangari K. Raveendran; Mohd Zainal Abdin Ab Kadir (Institute of Advanced Engineering and Science, 2021)
Hot spot as well as top oil temperatures have played the most effective parameters on the life of the electrical transformers. The prognostication of these factors is very vital for determining the residual life of the electrical transformers in the transmission and distribution systems. Thus, an accurate mathematical method is required to calculate the critical temperature such as hot spot and top oil temperature based on the different types of thermal models. In this study calculates the service life of the transformers based on an accurate top oil temperature. Accordingly, An approach solution is given for calculating the thermal model. Also, findings are validated with true temperatures. Finally, this method is implemented on 2500 KVA electrical transformer.